"Don't Leave Us Behind": The Importance of Mentoring for Underrepresented Minority Faculty. (February 2015) - Zambrana, Ruth Enid; Ray, Rashawn; Espino, Michelle M.; Castro, Corinne; Douthirt Cohen, Beth; Eliason, Jennifer
This article examines the mentoring experiences of 58 underrepresented minority (URM) faculty at 22 research-extensive institutions. Drawing on in-depth interviews and focus group data, participants discussed the importance of mentoring across the life course, the ideal attributes of mentoring relationships, the challenges to effective mentoring, and the role of political guidance. These data elicited three main themes regarding mentoring: (a) Life course practices geared toward accumulating social capital are critical, (b) major barriers are linked to the undervaluing of faculty research areas and community-engaged scholarly commitments, and (c) connections with mentors who understand the struggles specific to URMs at predominantly White institutions (PWIs) can assist with retention and success. This study provides a roadmap for shifting how we engage with URM faculty and strategies and knowledge to assess the effectiveness of mentoring to increase the retention of URM faculty.